42: Vitamin D Exposure During Pregnancy and Early Childhood and Risk of Childhood Wheezing. Issue 5 (1st June 2015) - Anderson, L; Chen, Y; Omand, J; Birken, C; Parkin, P; To, T; Maguire, J
Abstract: BACKGROUND: The association between vitamin D and wheezing in early childhood is unclear. OBJECTIVES: The primary objective was to evaluate the association between vitamin D exposure, during both pregnancy and childhood, and early childhood wheezing. Secondary objectives were to evaluate the associations between vitamin D exposures and early childhood asthma and wheezing severity. DESIGN/METHODS: We conducted a cohort study of children (0 to 5 years) recruited from 2008-2013 through the TARGet Kids! primary care research network. Vitamin D exposures included: maternal vitamin D supplement use during pregnancy, child vitamin D supplementation, and children's 25-hydroxyvitamin D (25(OH)D) concentrations. Outcomes measured were parent reported childhood wheezing, diagnosed asthma and wheezing severity. Vitamin D supplement and wheezing data were available on 2478 children and blood samples were available on 1275 children. Adjusted odds ratios (aOR) and 95% confidence intervals (CI) were estimated using logistic regression adjusted for age, sex, ethnicity, body mass index, birthweight, outdoor play, breastfeeding duration, daycare status, parental smoking and asthma family history. RESULTS: Vitamin D supplementation during pregnancy was associated with lower odds of childhood wheezing (aOR=0.65; 95% CI 0.46–0.93). In early childhood, neither 25(OH)D (aOR per 10 nmol/L =1.01, 95% CI 0.96–1.06) nor vitamin D supplementation (aOR=1.00; 95% CI 0.81–1.23) were associated with wheezing. No significant associations were observed with diagnosed asthma or wheezing severity. CONCLUSION: Vitamin D supplementation during pregnancy was associated with reduced odds of wheezing but child vitamin D supplementation during childhood and childhood 25(OH)D were not associated with wheezing. The timing of exposure may be important in understanding the association between vitamin D and childhood wheezing.